Nanotechnology and human health - Malsch, Ineke; Emond, Claude (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
'Preface: Nanotechnology and Human Health presents scientific and technical developments in nanotechnology for applications in three areas that are expected to lead to impacts on human health: biomedical (pharmaceuticals and medical devices), agrifood and water, and the environment. This technical core is preceded by an introduction including information on current nanotechnology research programs in industrialized countries and emerging economies. Apart from opportunities of nanotechnology for human health, toxicological aspects and life cycle risks and impacts are reviewed. The volume is completed with an analysis of ethical, legal, and social implications of bionanotechnology, and a concluding analysis. The collection of discussions of current nanotechnology for the abovementioned three areas together with environment, health, safety aspects, and ethical and societal implications provides the reader a unique insight into contemporary technological developments and what they may mean for human health. The work has a sound scientific basis, thereby avoiding unrealistic predictions. At the same time, analysis of societal implications is not usually included in most technical books about trends in nanotechnology. By including these aspects, the reader with a technical or natural science background is encouraged to be more responsible in R & D on nanotechnology that will have an impact on human health. The reader with a social science background can benefit because the technical reviews are written for a nonspecialist audience, taking care to explain terminology. The societal aspect chapters are intended to contribute to contemporary debates in social studies of science and at the same time be accessible to nonspecialists'--
Nanomaterial characterization and metrology / Asmus Meyer-Plath and Florian F. Schweinberger -- Nanoparticles : new medical potential today and tomorrow / Tamar Chachibaia -- Nanomaterials for bone reconstructive composites / M. van der Zande, B.C. Chesnutt, X.F. Walboomers, and J.A. Jansen -- Nanotechnologies in agrofood and water / Frans W.H. Kampers -- Nanofoods : environmental, health, and socioeconomic risks or the Achilles heel of nanotechnologies? / Simon Beaudoin, Louise Vandelac, and Christian Papilloud -- Benefits of nanotechnology for the environment / Danail Hristozov -- In vitro study for nanomaterials / Seishiro Hirano and Karim Maghni -- Toxicokinetics and interaction of nanoparticles with biological matrices / Claude Emond -- Environmental fate and ecotoxicology of nanomaterials / Bernard Lachance, Mahsa Hamzeh, and Geoffrey I. Sunahara -- Life cycle risks and impacts of nanotechnologies / Olivier Jolliet, Ralph K. Rosenbaum, and Alexis Laurent -- Anticipating ethical legal and social aspects of emerging technologies gaps in innovation chain : the case of body area networks / Alireza Parandian -- Capability approach to nanotechnology for sustainable development / Ineke Malsch.
Includes bibliographical references and index.
Keywords: Nanotechnology; Biomedical Technology; Environment; Nanostructures